Rural and Urban Agri-Food Vendors Survey in Bangladesh - Jaman, Ahmed; Rashid, Harun; Dhar, Palash; Ali, Hazrat; Khondker, Murshed-E-Jahan; Tabassum, Sumaya (2025)
The CGIAR initiative on Asian Mega-Deltas (AMD) has conducted a Rural and Urban Agri-Food Vendors Survey in Bangladesh. This survey aims to provide researchers a comprehensive understanding of the transformative changes, climate and gender issues, and food loss and waste management within the agri-food system in the Southwest Bangladesh. The findings from this survey will help policymakers and NGOs identify policies or strategies to improve the agri-food system's supply chain in Bangladesh. The survey covers approximately 750 food vendors across six districts in Bangladesh.